On the millimetre continuum flux–radius correlation of proto-planetary discs. (2nd May 2019) - Rosotti, Giovanni P; Booth, Richard A; Tazzari, Marco; Clarke, Cathie; Lodato, Giuseppe; Testi, Leonardo
Abstract: A correlation between proto-planetary disc radii and sub-mm fluxes has been recently reported. In this letter, we show that the correlation is a sensitive probe of grain growth processes. Using models of grain growth and drift, we have shown in a companion paper that the observed disc radii trace where the dust grains are large enough to have a significant sub-mm opacity. We show that the observed correlation emerges naturally if the maximum grain size is set by radial drift, implying relatively low values of the viscous α parameter ≲0.001. In this case, the relation has an almost universal normalization, while if the grain size is set by fragmentation the flux at a given radius depends on the dust-to-gas ratio. We highlight two observational consequences of the fact that radial drift limits the grain size. The first is that the dust masses measured from the sub-mm could be overestimated by a factor of a few. The second is that the correlation should be present also at longer wavelengths (e.g. 3mm), with a normalization factor that scales as the square of the observing frequency as in the optically thick case.